Stomach Content Analysis of Anabas testudineus in The Teluk Petai Lake Siak Hulu Sub-regency Kampar regency Riau Province - Arisa Trinovira Barus; Deni Efizon; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTAnabas testudineus is one of the freshwater fishes that can be found in the Teluk Petai Lake. The research aimed to find out the type of food consumed by that fish has been conducted from October to November 2020. Sampling is done 4 times at intervals of time once a week. The number of fish caught during the study was 95, but 17 of them had empty stomachs and they cannot be analyzed. The analysis was conducted using a volumetric method. Stomach content was analyzed as a basis to calculate the Preponderance Index. Results shown that the main food of the fish in Teluk Petai Lake was insects (52,80%), the additional food were plants (22,70%) and fishes (17,23%), and the complementary food was phytoplankton (7,28%). The small fishes (total length range 85-97 mm) food composition has more plant type than insects and the big fishes (total length range 163-170 mm) food composition has more insects type than plants. Data obtained indicate that A. testudineus can be categorized as an omnivorous fish.Keywords: Teluk Petai Lake, Anabas testudineus, Stomach Content Analysis, Preponderance Index